2008
DOI: 10.1128/jvi.01912-07
|View full text |Cite
|
Sign up to set email alerts
|

Human Immunodeficiency Virus Type 1 Gag Engages the Bro1 Domain of ALIX/AIP1 through the Nucleocapsid

Abstract: Human immunodeficiency virus type 1 (HIV-1) and other retroviruses harbor short peptide motifs in Gag that promote the release of infectious virions. These motifs, known as late assembly (L) domains, recruit a cellular budding machinery that is required for the formation of multivesicular bodies (MVBs). The primary L domain of HIV-1 maps to a PTAP motif in the p6 region of Gag and engages the MVB pathway by binding to Tsg101. Additionally, HIV-1 p6 harbors an auxiliary L domain that binds to the V domain of AL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
159
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(166 citation statements)
references
References 55 publications
7
159
0
Order By: Relevance
“…2E and column 5 of Fig. 2G), indicating that the reported interaction between the NC domain of Gag and Bro1 domain of ALIX (45,46) was not sufficient to recruit detectable levels of ALIX in this system. The ALIX PRD contains a P(S/T)AP motif that is capable of binding to the TSG101 subunit of ESCRT-I (18), although the motif is not essential for ALIX function in HIV-1 budding (19,20).…”
Section: Resultsmentioning
confidence: 97%
“…2E and column 5 of Fig. 2G), indicating that the reported interaction between the NC domain of Gag and Bro1 domain of ALIX (45,46) was not sufficient to recruit detectable levels of ALIX in this system. The ALIX PRD contains a P(S/T)AP motif that is capable of binding to the TSG101 subunit of ESCRT-I (18), although the motif is not essential for ALIX function in HIV-1 budding (19,20).…”
Section: Resultsmentioning
confidence: 97%
“…2A). The YLCL motif could potentially interact with AIP1, which was also demonstrated to bind viral nucleocapsid proteins (31,37) and to regulate the transport of nucleocapsids from endosomes to the cytosol (25). To test whether this YLCL motif plays a role in VLP release or NP incorporation into VLPs, we generated a Z mutant in which YLCL was changed to AAAA ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Analysis of Marburg virus NP revealed several putative late domains, one of which recruits TSG101 to the budding sites, resulting in enhanced VLP formation (12). Similarly, the zinc finger of the HIV-1 nucleocapsid domain of Gag has been shown to bind AIP1, cooperating with the late domains to employ the ESCRT pathway for viral budding (13,37). Here, we demonstrated that Mopeia virus uses an ESCRT-associated protein, AIP1, for NP incorporation into virions; the use of the ESCRT pathway for NP incorporation into virions has not been shown for any other virus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence suggests that Gag ubiquitination is important for virion assembly and viral infectivity [11,10]. Ubiquitination is thought to allow Gag to interact with and co-opt members of the endosomal sorting system (the ESCRT complexes [14]) for the purposes of virion production [9,7,21]. The trans-Golgi network-associated protein SH3RF1 (hPOSH) is the only E3 ubiquitin ligase known to directly interact with Gag, but it's unlikely to ubiquitinate Gag itself [1].…”
Section: Discussionmentioning
confidence: 99%